Long-range exciton transport in brightly fluorescent furan/phenylene co-oligomer crystals. Issue 1 (6th November 2018) - Mannanov, Artur A.; Kazantsev, Maxim S.; Kuimov, Anatoly D.; Konstantinov, Vladislav G.; Dominskiy, Dmitry I.; Trukhanov, Vasiliy A.; Anisimov, Daniil S.; Gultikov, Nikita V.; Bruevich, Vladimir V.; Koskin, Igor P.; Sonina, Alina A.; Rybalova, Tatyana V.; et al.
Abstract : Long-range exciton diffusion facilitates efficient exciton harvesting in a lightly-doped organic semiconductor crystal. Abstract : The design of light-emitting crystalline organic semiconductors for optoelectronic applications requires a thorough understanding of the singlet exciton transport process. In this study, we show that the singlet exciton diffusion length in a promising semiconductor crystal based on furan/phenylene co-oligomers is 24 nm. To achieve this, we employed the photoluminescence quenching technique using a specially synthesized quencher, which is a long furan/phenylene co-oligomer that was facilely implanted into the host crystal lattice. Extensive Monte-Carlo simulations, exciton–exciton annihilation experiments and numerical modelling fully supported our findings. We further demonstrated the high potential of the furan/phenylene co-oligomer crystals for light-emitting applications by fabricating solution-processed organic light emitting transistors.